2000
DOI: 10.1002/1098-2388(200007/08)19:1<11::aid-ssu3>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Current management of epithelial ovarian carcinoma: A review

Abstract: Epithelial carcinoma of the ovary is the most lethal of gynaecological malignancies and it affects about one in 70 women in developed countries. Over 75% of women with the disease have tumour spread beyond the pelvis at the time of diagnosis, and their treatment requires the appropriate use of surgery and chemotherapy. The strategies used in the treatment of ovarian cancer are constantly evolving. An overview of current treatment regimens and their evolution is provided, with particular emphasis on the interde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 108 publications
0
40
0
2
Order By: Relevance
“…15 All patients diagnosed with what appears to be resectable disease undergo surgery with the intent of performing optimal abdominopelvic cytoreductive surgery. We believe that a maximal surgical effort should be employed, and we recently reported a statistically significant increase in optimal debulking rates at our institution by incorporating extensive upper abdominal procedures into our surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…15 All patients diagnosed with what appears to be resectable disease undergo surgery with the intent of performing optimal abdominopelvic cytoreductive surgery. We believe that a maximal surgical effort should be employed, and we recently reported a statistically significant increase in optimal debulking rates at our institution by incorporating extensive upper abdominal procedures into our surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, it was estimated that 20 180 women will be diagnosed with ovarian cancer, and 15 310 will die of the disease (Jemal et al, 2006). The standard of care in the treatment of patients with advanced-stage epithelial ovarian cancer includes primary cytoreduction surgery, followed by a platinum-based chemotherapy regimen (Marsden et al, 2000;Bristow et al, 2002).…”
mentioning
confidence: 99%
“…[1][2][3][4] In most autopsy reports from the last 3 decades that deal with the metastatic pattern of EOC the uterus is not listed as a metastatic site [6][7][8][9][10] probably because the patients underwent a hysterectomy before they died of the disease. In only one study of 100 autopsies of ovarian cancer 11 it is reported that the uterine serosa, the myometrium and the cervix were involved in 27%, 10%, and 3% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] However, to the best of our knowledge, the rationale for hysterectomy at the initial operation is not clear. Possible reasons might be a high frequency of uterine involvement by the tumor and its potential impact on survival.…”
Section: Introductionmentioning
confidence: 99%